Sanksi Pidana Terhadap Pelaku Pencemaran Limbah Industri di Sungai - Kadek Agung Yudha Mahadewa; I Nyoman Gede Sugiartha; I Putu Suwantara (Fakultas Hukum Universitas Warmadewa, 2024)
Environmental pollution is one of the factors of environmental damage. The development of environmental problems with inadequate law enforcement is becoming increasingly severe. Based on the background, the problem formulation is: What are the legal regulations regarding industrial waste pollution in rivers? What are the criminal sanctions for perpetrators of criminal acts of industrial waste pollution in rivers? The aim of the research is to regulate the law regarding industrial waste pollution in rivers. To find out criminal sanctions against perpetrators of criminal acts of industrial waste pollution in rivers. This thesis research uses normative juridical research methods, with a library approach. Sources of legal materials consist of primary, secondary and tertiary legal materials. The research results show that regulations regarding industrial waste pollution in rivers are regulated in the 1945 Constitution, UURI No. 4/1982 concerning the basic provisions of environmental management to UURI No. 23/1997 concerning environmental management, UURI No. 32/2009 concerning environmental protection and management, PP No. 22/2021 2021 Concerning the Implementation of Environmental Protection and Management. There are two types of sanctions against perpetrators of industrial waste pollution in rivers, namely criminal sanctions and administrative sanctions. UURI No. 32/2009 concerning Environmental Management and Protection provides administrative sanctions from Article 76 to Article 83 of the UUPPLH and criminal sanctions regulated in Chapter XV, namely from Article 97 to Article 120 of the UUPPLH. Sanctions against perpetrators of waste pollution who do not follow the regulations regarding B3 waste management are contained in article 102.